The Phenomenon of Young Marriage from a Hadith Perspective - Maya Veronica; Faiqa Dzakira (Jurnal Riset Agama, 2022)
This study aims to discuss the phenomenon of young marriage from a hadith perspective in Lemahmulya Village. This study uses a mixed-method approach by applying a descriptive analytical-critical method. The object of research is the phenomenon of young marriage that occurs in Lemahmulya Village. The subject of this research is of course the persons of young marriage which consists of three categories of factors causing it. The results and discussion of this study indicate that the phenomena that occur in Lemahmulya Village consist of three categories of factors, namely the low economic and educational factor, the accident factor due to promiscuity, the self-will factor and religious observance. This study concludes that the phenomenon of young marriage that occurred in Lemahmulya Village from the perspective of hadith in terms of practice does not conflict with religious rules because it has benefits for each perpetrator and with the dispensation given by the court with very urgent reasons accompanied by sufficient supporting evidence then The young marriage that took place in Lemahmulya Village also did not violate state law. However, it is necessary to reconsider the impacts caused by young marriage.